Football fun - Omoth, Tyler (2021)
"Football is fun watch, but even more fun to play! Kids can get in the game by learning about the rules of the sport, the equipment needed to play, and the importance of good sportsmanship. Then they can practice a key football skill to have even more fun on the field"--
What is football? -- What do I need to play? -- Where do I play? -- How do I play? -- How can I be a good sport?
Includes bibliographical references and index.
Ages 5-7
Grades K-1
Keywords: Football -- Juvenile literature; Sportsmanship -- Juvenile literature